Topological pumping in Aharonov – Bohm rings - Haug, Tobias (2020)
Topological Thouless pumping and Aharonov–Bohm effect are both fundamental effects enabled by the topological properties of the system. Here, we study both effects together: topological pumping of interacting particles through Aharonov–Bohm rings. This system can prepare highly entangled many-particle states, transport them via topological pumping and interfere with them, revealing a fractional flux quantum. The type of the generated state is revealed by non-trivial Aharonov–Bohm interference patterns that could be used for quantum sensing. The reflections induced by the interference result from transitions between topological bands. Specific bands allow transport with a band gap scaling as the square-root of the particle number. Our system paves a new way for a combined system of state preparation and topological protected transport.